12-HETE is a regulator of PGE2 production via COX-2 expression induced by a snake venom group IIA phospholipase A2 in isolated peritoneal macrophages - Moreira, Vanessa (2020)
The snake venom myotoxin (MT)-III is a group IIA secreted phospholipase A2 (sPLA2) with pro-inflammatory activities. Previous studies have demonstrated that MT-III has the ability to stimulate macrophages to release inflammatory lipid mediators derived from arachidonic acid metabolism. Among them, we highlight prostaglandin (PG)E2 produced by the cyclooxygenase (COX)-2 pathway, through activation of nuclear factor (NF)-κB. However, the mechanisms coordinating this process are not fully understood. This study investigates the regulatory mechanisms exerted by other groups of bioactive eicosanoids derived from 12-lipoxygenase (12-LO), in particular 12-hydroxyeicosatetraenoic (12-HETE), on group IIA sPLA2-induced (i) PGE2 release, (ii) COX-2 expression, and (iii) activation of signaling pathways p38 mitogen-activated protein kinases(p38MAPK), protein C kinase (PKC), extracellular signal-regulated kinase 1/2 (ERK1/2), and NF-κB. Stimulation of macrophages with group IIA sPLA2 resulted in release of 12-HETE without modification of 12-LO protein levels. Pre-treatment of these cells with baicalein, a 12-LO inhibitor, decreased the sPLA2-induced PGE2 production, significantly reduced COX-2 expression, and inhibited sPLA2-induced ERK; however, it did not affect p38MAPK or PKC phosphorylation. In turn, sPLA2-induced PGE2 release and COX-2 expression, but not NF-κB activation, was attenuated by pre-treating macrophages with PD98059 an inhibitor of ERK1/2. These results suggest that, in macrophages, group IIA sPLA2-induced PGE2 release and COX-2 protein expression are distinctly mediated through 12-HETE followed by ERK1/2 pathway activation, independently of NF-κB activation. These findings highlight an as yet undescribed mechanism by which 12-HETE regulates one of the distinct signaling pathways for snake venom group IIA sPLA2-induced PGE2 release and COX-2 expression in macrophages.